2008
DOI: 10.1136/ard.2007.082495
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation improves microcirculation in systemic sclerosis

Abstract: These results indicate that HSCT with a high dose CYC regimen may foster vascular remodelling, while CYC at lower doses and with a chronic regimen does not influence the microvasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 21 publications
1
76
0
6
Order By: Relevance
“…Besides the action of conditioning immunosuppressive therapy in ablating autoimmune response and strongly reducing fibroblast activation (1), it has been postulated that the ASCT effectiveness can be at least in part ascribed to the capacity of the repopulating stem cells to induce a neoangiogenesis in the sclerotic skin (13,23).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the action of conditioning immunosuppressive therapy in ablating autoimmune response and strongly reducing fibroblast activation (1), it has been postulated that the ASCT effectiveness can be at least in part ascribed to the capacity of the repopulating stem cells to induce a neoangiogenesis in the sclerotic skin (13,23).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that after hematopoietic stem cell transplantation, in beforehand avascular regions of the nailbed, a new formation of vessels, e.g. giant capillaries, could be observed (68).…”
Section: Clinical Implications -Supporting Repairmentioning
confidence: 99%
“…Severe nailfold capillaroscopy (NC) findings have been described but their association with disease activity and/or response to treatment have rarely been investigated [1][2][3][4][5][6][7] .…”
mentioning
confidence: 99%